Emosi Negatif dalam Pembelajaran Matematika: Studi Deskriptif dan Komparatif Antar Tingkatan Kelas Berdasarkan Perspektif Teori Sosiokultular Vygotsky - Khotimah, Husnul; Muntazhimah, Muntazhimah (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2025)
This study aims to explore students' negative emotions in learning mathematics at the Vocational High School (SMK) level using Vygotsky's Sociocultural Theory perspective. It analyzes five types of negative emotions and compares them across different grade levels. The research employs a descriptive and comparative quantitative method involving 60 students from three grade levels at SMK Tangerang Global. Data were collected using AEQ-M and analyzed with descriptive statistics and ANOVA, while Vygotsky's Sociocultural Theory was used to interpret how social interaction and the cultural context in the classroom affect students' emotions. The results indicate that students' average level of negative emotions falls into the moderate category (2.19 on a 5-point scale), with the main triggering factors being shame, fear of making mistakes, and boredom with the material. From the perspective of Vygotsky's Sociocultural Theory, these negative emotions suggest a lack of collaboration and social interaction, which can hinder the utilization of the Zone of Proximal Development (ZPD). Therefore, collaborative learning strategies, scaffolding, and relevant contexts are recommended to create a more supportive learning environment. This study provides valuable insights into the dynamics of students' negative emotions in mathematics learning and offers approaches to enhance a more effective and inclusive learning experience.